2021
DOI: 10.1097/scs.0000000000008366
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Imaging Investigation of Tongue Movement Patterns of Cleft-Related Lateralized and Palatalized Misarticulation

Abstract: natriuretic peptide (BNP) was 548.4 pg/ml and gradually increased to 979.47 pg/ml. Comprehensive data suggest that the patient has cardiac insufficiency. Control of the ventricle rate to prevent stroke. Strictly control the 24-hour access volume to avoid water and sodium retention. Give medicines to strengthen the heart, diuresis, and improve heart function.On the 11th postoperative day, the patient had a sudden decrease in consciousness and a decrease in the muscle strength of the right limb (Grade II). Compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…LM is known to be caused by abnormal tongue movement patterns, 3,7 but tongue movement during articulation is difficult to confirm visually. Several techniques have been employed to observe tongue movement in LM, including X-rays, 6,7,12 ultrasound, [13][14][15] and electropalatography (EPG). 2,3,[5][6][7][8]12,16,17 However, X-rays are associated with radiation exposure, and ultrasound systems do not allow the synchronization of images and sound or quantified analysis.…”
Section: Introductionmentioning
confidence: 99%
“…LM is known to be caused by abnormal tongue movement patterns, 3,7 but tongue movement during articulation is difficult to confirm visually. Several techniques have been employed to observe tongue movement in LM, including X-rays, 6,7,12 ultrasound, [13][14][15] and electropalatography (EPG). 2,3,[5][6][7][8]12,16,17 However, X-rays are associated with radiation exposure, and ultrasound systems do not allow the synchronization of images and sound or quantified analysis.…”
Section: Introductionmentioning
confidence: 99%
“…C left-related lateral misarticulation is a common type of speech sound disorder (SSD) and also common speech disorder after cleft palate surgery, 1 and children with it have difficulty understanding semantics compared to other children of the same age. [2][3][4] It has been reported that children over 2 years old should have a clarity rate of around 50%, and those aged 2-2, and 6 should be able to speak more than 50 single words or phrases.…”
mentioning
confidence: 99%
“…12 This type of speech disorder after cleft palate surgery is very common in preschoolers and adolescents. 1 In daily clinics, patients who seek medical treatment are children with speech or language problems, which seriously affect their learning, life, communication, and interaction. 13 In this study, we randomly selected 126 children who were diagnosed with lateral misarticulation after cleft palate surgery and received treatment at the Speech and Language Disorder Diagnosis and Treatment Center of the First Affiliated Hospital of Harbin Medical University from 2021 to 2023.…”
mentioning
confidence: 99%
See 1 more Smart Citation